Blood transcriptional signatures of gallstone pathogenesis in patients with cholelithiasis and choledocholithiasis (Annals of Medical Research, 2022)
Aim: Disease-specific molecular signalling in peripheral blood has the potential to inform on pathophysiological mechanisms of diseases. Here, we aimed to investigate the blood-based gene expression profiles that reflect disease-specific pathogenic mechanisms of gallstones, such as antioxidant defence, heat-shock responses, DNA damage and repair, ABC pump mechanisms, mucin signals, mitochondrial dysfunction and apoptosis in patients with Cholelithiasis (CHL) and Choledocholithiasis (CHDL)Materials and Methods: The relative fold-change in the mRNA expression levels of 73 genes were analysed using a gallstone-related qRT-PCR array in 10 control individuals, 24 CHL patients and 23 CHDL patients. Serum malondialdehyde levels was determined by thiobarbituric-acid reactive substance assays, and 8-hydroxy-2’-deoxyguanosine levels was determined by ELISA assays.Results: Our results showed that peripheral whole blood gene expression profile strongly reflects tissue specific molecular signalling in gallstone pathogenesis. The present findings of altered gene expressions including antioxidant defence (CuZn-SOD, CAT), heat shock protein (HSP70), DNA repair (MLH1 and RAD18), pro-apoptotic (P53, BAX, Cyt-c and Caspase 3), ABC transporter (ABCB1, ABCC2, and LRP1) and Mucin signals (MUCIN4, MUCIN5AC and MUCIN5B) point out to DNA damages via oxidative stress as well as deteriorating ABC types pump mechanisms and mucin signals in CHL and CHDL patients. Our findings may also suggest that activation of mitophagy activator, DRP1/hFIS1/PINK1 axis induced by oxidative stress and DNA damage may have a role in the pathogenesis of CHL and CHDL.Conclusion: Our results indicate that a blood-based gene expression signature has promising accuracy for monitorize pathogenesis of disease in CHL patients, CHDL patients and unaffected controls.
Keywords: Blood; Gallstone; Gen expressions; Mucin; ABC transporter; Mitochondrial dysfunction